”AIR” SEBAGAI SARANA PENINGKATAN IMTAQ (INTEGRASI KIMIA DAN AGAMA) - Pangoloan Soleman Ritonga (Lembaga penelitian dan pengabdian kepada Masyarakat, 2011)
Glory to Allah, water is a mercy and grant from Allah praise be unto thee the almighty. al-Quran explains that water is source of life where Allah stimulate growth and breed plants and animals with water. It has different cristal geometry depend on treatment. The crystal is looked beautiful, is we always say repeatedly chant part of the confession of faith. On the other hand, the crystal is looked bad. If we always say curses and obscenities. Glory to Allah, Acording to chemistry water has formula H2O molecule that has a bundle of hydrogen. It is as a proven of Allah the cherisher and sustainer of the world. Without a bundle of hydrogen in water, water will melt aroun -100oC and boil -90oC. In short, we have never seen and found water again and it has happened juggement day.